The Austrian way: Director conduct in the context of legal and cultural frameworks of corporate governance - Bickley, Maureen; Nowak, Margaret (Elsevier, 2005)
In recent years there has been considerable discussion of and some movement towards harmonisation of governance structures and processes between EU and North America in particular. Multilateral organisations such as the World Bank together with the expansion of the EU in 2004 have provided added impetus for a broader focus on harmonisation. At the same time, emanating from the USA, the requirement to confirm to Sarbanes Oxley has exerted unilateral pressure on individual corporations worldwide. The authors argue, however, that a "one size fits all" approach to governance is not consistent with the different cultural values, frameworks and legal systems which are the various national contexts of governance. These differences are consistent with alternate paradigms concerning the motivation and behaviours of directors. It is further argued that these differences are relevant to discussion of corporate sustainability. The authors note that the theoretical models, agency theory and stewardship theory, are each consistent with alternative accountability approaches and thus different approaches to director motivation. A qualitative study of Austrian company directors is used to investigate whether the recent development of a more open economy coupled with the global capital market is generating a convergent model of director conduct. It was apparent that a stakeholder approach, where stewardship theory best explains the processes to mediate director conduct, continues to best describe the Austrian way. This contrasts with "theory in use" in Anglo/US practice which conforms to the tenets of Agency theory. We conclude with a discussion of the implications for sustainability management.